Fabrica Societatis. No. 2/2019 : Spis treści (Instytut Socjologii Uniwersytetu Wrocławskiego, 2019)
Fabrica Societatis is a scientific journal whose fundamental goal is to create a space for considerations of theoretical, methodological and empirical nature which aim at acquiring knowledge of everyday measures manufacturing and shaping various displays of everyday life. It is also a journal for publishing articles that appreciate the uniqueness of individual experience and that change perspectives in order to go beyond the social clichés. Such attempts require brave explorations and asking questions for which so far there has not been answers. Hence, the journal is an open space for both experienced researchers and beginners; for the finished projects and ideas that have just started to take their shape; for any and all undertakings that offer a chance to enrich the sociological knowledge and to widen the interdisciplinary horizons. This is the second issue of the journal. It focuses on three areas. The first one is related to intimacy, sexuality and relationships. Five different authors analyse various forms of sexual intimacy, all of the different status: from performed, through postulated, to recommended. This part of the journal is closed with an interesting and brave proposal. The second area is the result of the seminar that took place at the Institute of Sociology, University of Wrocław, to celebrate the 100th anniversary of women’s suffrage in Poland. Apart from the introductory article prepared by the organiser of the seminar, we present here two other papers of its participants: the first one regarding the women’s reformist milieus and legal associations acting in the Weimar Republic and then the Federal Republic of Germany for the equal rights of men and women; the second one regarding the conditions of the development of Polish feminism at the turn of the 19th and 20th centuries. The third and last area is represented by three articles devoted to the lifestyle and emotions: from the strategies on the pursuit of beauty in Polish People’s Republic; through the heroes of the popular culture serving as the mirrors of social emotions; to expressive activities of the disabled investigated from the perspective of the social capital.
Keywords: human geography; bricolage; feminism; adaptive strategies in everyday life; same-sex family; disabilities; sex services; expressive actions; instrumental actions; erotic literature; emotions; emancipation; history of women; women’s voting rights; clients’ sexual needs and forms of sexual activity; intimacy; lesbian studies; equal rights; beauty standards; friendship with benefits; geographies of sexualities; hero; hookup culture; homo eligens; relationality; values; prostitution; sexuality; gender; homo egens; social capital